A classificação internacional para a prática de enfermagem no processo de cuidar : significados atribuídos por docentes e graduandos de enfermagem - Pfeilsticker, Débora Catarina (2006)
The study aims at understanding the meanings attributed by Nursing teachers and graduating students referring to the International Classification for Nursing Practice (ICNP®) in the care process. The data collection uses the focal group technique with seventeen graduating students – a session with two distinct groups – and an individual interview with five teachers of a private institution of higher education of Vitória district in the State of Espírito Santo. For data analysis, it uses the technique of analyzing content and it discusses the results based on four dimensions – praxiologic, communicative, cognitive and political. The conceptions revealed by the teachers and pupils indicated potentialities and limits of ICNP®. That classification was shown as an instrument able to promote care organization and quality of assistance, it contributes for the autonomy and professional self-confidence, and it provides visibilities for the Nursing practices and values the profession. As limits for the ICNP® use, the resistance to the referential change, the lack of theoreticalconceptual control for its use and the lack of institutionalized models of the Nursing Process were reported. In conclusion, the ICNP® was seen by the project members as a possible model for the care process and that system structure of classification contributes for the development of the clinical reasoning, facilitating the Systematization of the Nursing Assistance.